lncRNA MIR210HG promotes the progression of endometrial cancer by sponging miR-337-3p/137 via the HMGA2-TGF-β/Wnt pathway - Jian Ma; Fan-Fei Kong; Di Yang; Hui Yang; Cuicui Wang; Rong Cong; Xiao-Xin Ma (Elsevier, 2021)
Epithelial-mesenchymal transition (EMT) promotes tumorigenesis and metastasis and increases tumor tolerance to treatment intervention. Abnormal activation of transforming growth factor β (TGF-β) and Wnt pathway induces EMT. Long non-coding RNAs (lncRNAs) significantly influence EMT regulation. Herein, we show that MIR210HG is overexpressed in endometrial cancer tissues, which is associated with poor prognosis. MIR210HG silencing significantly inhibited proliferation, migration, invasion, and EMT phenotype formation in vitro as well as tumorigenesis in vivo. Mechanistically, bioinformatics analyses, RNA binding protein immunoprecipitation (RIP) assays, and luciferase assays showed that MIR210HG acts as a molecular sponge of miR-337-3p and miR-137 to regulate the expression of HMGA2. Additionally, MIR210HG overexpression significantly enriched the Wnt/β-catenin and TGF-β/Smad3 signaling pathway genes, while MIR210HG or HMGA2 knockdown suppressed the Wnt/β-catenin and TGF-β/Smad3 signaling pathway. Our findings on the MIR210HG-miR-337-3p/137-HMGA2 axis illustrate its potential as a target for endometrial cancer therapeutic development.